: A NOVEL APPROACH TO DETECT THE SHORTEST PATH FOR SECURE DATA AGGREGATION USING FUZZY LOGIC IN WIRELESS SENSOR NETWORKS (International Journal of Engineering and Computer Science, 2017)
Wireless Sensor Networks have numerous nodes with limited energy in a particular area. It is one of the major issues is increasing the network life time. Secure data aggregation is a challenging task in Wireless Sensor Network. This issue needs to be overcome using efficient technique. An energy efficient scheme needs to be proposed to detect the shortest path for data transmission using fuzzy logic. The Sensor Nodes death frustrates and the problem gets aggravated if the cluster node fails. When a cluster node fails because of energy depletion an alternative cluster needs to be chosen for that particular region. In periodical time each sensor node in the cluster should possess the next cluster head re-election based on energy to avoid node failure. In this paper a novel technique is proposed using Fuzzy to find the shortest path for data aggregation based data transmitted technique It is shown that the proposed technique has improved the throughput with reduced packed drop and also less energy consumption in these networks. Our Technique is evaluated through NS2 Network Simulator.